Experimental investigation of the mechanical properties of woven abaca (Musa textilis) fiberreinforced epoxy composites - Efriyohadi, Agung; Cionita, Tezara; Siregar, Januar Parlaungan; Mohamed Reza Zalani, Mohamed Suffian; Fitriyana, Deni Fajar; Doni Widodo, Rahmat; Al Ichlas, Imran; Emad, Elsherif (EDP Sciences, 2024)
Abaca fiber which is also known as Musa textilis is a tropical banana species grown primarily for its fiber. It has several advantages when used as a reinforcement in polymer composites caused by its great mechanical performance, increase cellulose content, low cost, and abundant availability. It is important to note that the structure of the fibers used as reinforcing materials is a critical aspect of fabricating a strong polymer composite. Therefore, this study was conducted to determine the effects of layering as well as fiber orientation towards the mechanical characteristics of woven abaca-reinforced epoxy composites. Furthermore, this comprised the application of hand lay-up technique as well as hydraulic press molding in producing 2, 3, and 4 layers of woven abaca-reinforced epoxy composites after which the mechanical properties were analyzed based on its orientation in the warp and weft direction. The results showed that an increase in the number of layers from 2 to 4 did not affect the tensile and flexural properties at every layered stacking sequence of the fiber. Meanwhile, the material in the warp direction indicated a greater tensile as well as flexural properties in comparison to the weft direction. This means the number of layers and orientation of the woven abaca in epoxy composite possesses a significant influence towards the composites’ mechanical properties.